Characterization of geomorphological features of lunar surface using Chandrayaan-1 Mini-SAR and LRO Mini-RF data. (20th February 2021) - Vashishtha, Ankita; Kumar, Shashi
Abstract: The lunar surface comprises complex geomorphological features, which have been formed by the conjunction of processes namely impact cratering and volcanism. Geological features on the Lunar surface can be bifurcated into two main areas named Maria region and the Highland region. Taurus-Littrow valley, which was the Apollo-17 mission landing site, consisting of unique geomorphological characteristics by having a sample size of both Lunar Maria and Highland regions. The dielectric constant is a parameter that gives an approximate distribution of the constituent material of the target area. It is a complex quantity, which indicates a periodic variation of the electric field. The real part of dielectric constant indicates stored energy and the imaginary part indicates dielectric loss factor or the loss of the electric field in the medium due to continuous varying electric field. Planetary surfaces for which determining dielectric constant is an important analysis for most of the space missions, ground measurement is not feasible. This work includes the machine learning-based modeling of dielectric constant for the Apollo 17 landing site the Taurus-Littrow valley. Based on the surface roughness of the study area, two models Gaussian and Exponential have been implemented and compared for the modeled output of the dielectric constant values.The modeling approaches for dielectric characterization of the lunar surface were implemented on NASA's LRO Mini-RF SAR data and Mini-SAR hybrid-pol data of ISRO's Chandrayaan-1 mission. The coefficient of determination (r 2 ) and the root mean square error (RMSE) of the theoretical Gaussian model was 0.995, 0.042 and the Exponential model was 0.948, 0.1349 respectively. When compared with the already calculated values of dielectric constant from Apollo 17 return samples and literature survey, the Gaussian model gives a better variation. Gaussian model was further applied to the Lunar north pole crater namely Hermite-A crater, whose distinctive geomorphological characteristics and location being lunar north pole region, makes it one of the coldest places in the Solar System and a prominent location of water ice deposits.